Thymosin β4 in multiple myeloma: friend or foe - Caers, Jo; Otjacques, Eleonore; Hose, Dirk; Klein, Bernard; Vanderkerken, Karin (Annals of the New York Academy of Sciences, 2010)
Multiple myeloma (MM) is a malignancy characterized by the accumulation of monoclonal plasma cells in the bone marrow (BM). Because of the known involvement of thymosin β4 (Tβ4) in metastasis of tumor cells, we examined the expression and role of Tβ4 in MM disease. In a large patient population, we demonstrated that Tβ4 expression was significantly lower in myeloma cells compared to normal plasma cells and that patients with a high Tβ4 expression had a longer event free and overall survival. The decreased Tβ4 expression was also found in the murine 5TMM model. To study its function, we overexpressed the Tβ4 gene in 5T33MMvt cells by lentiviral transduction. These cells demonstrated a decreased proliferative capability and an increased sensitivity to apoptosis. Mice injected with Tβ4-overexpressing cells showed a prolonged survival compared to mice injected with controls. In contrast to its role in solid tumors, we found a decreased expression in myeloma cells compared to their normal counterpart and studies with overexpression of the Tβ4 gene indicated a tumor suppressive function of Tβ4 in myeloma development.
Gesehen am 23.03.2023
Thymosins in health and disease: 2nd International Symposium